2018
DOI: 10.4103/0973-1482.187367
|View full text |Cite
|
Sign up to set email alerts
|

Associations of interleukin-10 gene polymorphisms with acute myeloid leukemia in human (Egypt)

Abstract: IL-10 SNP at -819 was associated with enhanced AML risk, suggesting that rs1800871 provides clue for future studies and early detection of AML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…36 Similar results regarding this lack of effect on OS by IL-10 rs1800871 have been previously reported. 37 Pehlivan et al found no association between TNF-α rs1800629, IL-10 rs1800872, rs1800871, and rs1800896, IFN-γ rs2430561, and TGF-β1 rs1800470 (codons 10 and 25) polymorphisms and OS in their Turkish CML patients, 13 being therefore in line with our observations.…”
Section: Discussionsupporting
confidence: 90%
“…36 Similar results regarding this lack of effect on OS by IL-10 rs1800871 have been previously reported. 37 Pehlivan et al found no association between TNF-α rs1800629, IL-10 rs1800872, rs1800871, and rs1800896, IFN-γ rs2430561, and TGF-β1 rs1800470 (codons 10 and 25) polymorphisms and OS in their Turkish CML patients, 13 being therefore in line with our observations.…”
Section: Discussionsupporting
confidence: 90%
“…Infrared spectra were recorded in the range of wavenumbers 4000 to 650 cm −1 . Identification of each IR peak was conducted according to Shafik and Mayers et al…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that D. salina has a higher affinity for some heavy metal ions. It was shown that, under the same conditions, D. salina cells present high tendency for zinc accumulation, followed by copper and cobalt, the lowest tendency is for cadmium . This micro‐alga has a very high selectivity of the transport system for ferric ions, characterized by an unusual mechanism of iron acquisition .…”
Section: Introductionmentioning
confidence: 99%
“…In there, no association between IL10 (−1082G/A) and acute myeloid leukemia was detected [7]. Nevertheless, in the Egyptian population, −819 polymorphism was associated with enhanced risk [97]. In the Chinese population, the −819A allele frequencies in the AML group were higher than in the controls [98].…”
Section: Diseasementioning
confidence: 97%